The relationship between classroom climate and academic achievement of students considering the role of teacher-student interaction and academic motivation - hajar bahmaninejad; sakineh jafari (Allameh Tabataba'i University Press, 2018)
The purpose of the present study is to examine the mediating role of master - student interaction and motivation in the relation of classroom climate with students' academic achievement at the Semnan University. Regarding the purpose, the research methodology is practical and according to the method of data collection, it is considered as descriptive-correlation. The statistical community of the study consisted of all B.A and M.A, students of the Semnan University that 200 persons were selected by using cluster sampling method as the sample of the study (135 B.A students and 65 M.A students). All of them completed the scales of classroom climate, master - student interaction, motivation and students' academic achievement. The validity and reliability of the scales were assessed with The Cronbach's alpha. The findings showed that there is a significant positive relationship between the students' academic achievement with classroom climate, master - student interaction and motivation. The classroom climate has a direct and significant effect on students' academic achievement; also classroom climate has an indirect and significant effect on students' academic achievement with the mediation of master - student interaction. Classroom climate influences an indirect and significant effect with the mediation of motivation on students' academic achievement. The findings of this present show the importance of paying attention to classroom openness climate, master - student interaction and motivation on Increasing students' academic achievement.